Adaptive Resilience Building for Force Preservation to Battle Pandemic the Military Way - Rawat, Samir; Deshpande, Abhijit P.; Joshi, Priya; Boe, Ole; Piotrowski, Andrzej (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Resilience may be referred to as the capacity for positive adaptation and to quickly recover from difficulties and significant adversity. After examining operational definitions of related concepts, the article discusses resilience building exercises for functional fitness at the individual soldier level, to include among others, self-monitoring, self-evaluation, self-reinforcement, emotional regulation exercises, mindfulness training, relaxation and grounding exercises and importance of maintaining discipline and routine in the military. Using an acronym CARRIES, the article examines efforts to enhance resilience building through empirically validated cognitive, behavioural and intrapersonal skills originating from best practices learned in the military.